Medicinal Plants used by the Manobo Tribe of Prosperidad, Agusan Del Sur, Philippines-an Ethnobotanical Survey - Paraguison, Lyn Dela Rosa; Tandang, Danilo Niem; Alejandro, Grecebio Jonathan Duran (Asian Journal of Biological and Life Sciences, 2020)
Objectives:The Philippine Manobo tribe is historically rich in ethnomedicinal practices and known to use local names as “Lunas” (meaning cure) of most medicinal plants. The purpose of this study is to record the traditional practices, use of medicinal plants and information of the Agusan Manobo tribe in order to establish the relative significance, consensus and scope of all medicinal plants used.Methods:Ethnomedicinal survey of medicinal plants was carried out in three selected barangays of Prosperidad City, Agusan del Sur. Ethnomedicinal data were collected through a semi-structured interview, group discussions and guided field walks from 144 primary informants. Plant importance was calculated using indices such as Family importance value (FIV) and relative frequency of citation (RFC).Results:A total of 40 species belonging to 34 genera and 23 families have been identified as having ethnomedicinal significance. The highest FIV (97.27) in the treatment of body pain, hypertension and infection was reported for Asteraceae. The most commonly cited species of medicinal plants wereAnodendron borneenseKing and Gamble and Thottea sp.(RFC = 0.50) which is primarily usedfor treating gastrointestinal infection.Conclusion:The findings of this study show the rich ethnomedicinal tradition and knowledge of the cultural community of Agusan Manobo in Prosperidad City. Thus, for the potential management and conservation strategies of such plant genetic resources, recording these traditional knowledge of medicinal plants and practices is highly important. This indigenous legacy of awareness regarding medicinal plants will open pathways for future drug discovery to enhance global healthcare.
Keywords: Agusan Manobo; Ethnobotany; Medicinal plants; Prosperidad; Survey